Combination with temperature changes - Esh, C.; Carter, S.; Chrismas, B.; Taylor, L. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
Acute and chronic responses to hypoxic stimuli are well-defined in males, with applications in clinical and athletic perfomance settings across a range of exercise and health outcomes (as outlined within prior cahpters). However, limited data exists for females and people with a disability/para-athlete populations. Understanding of combined hypoxic stimuli with other environmental extremes (e.g., heat and cold) is less well defined. Given the limited literature exploring the effects of hypoxia, heat, and cold on exercise or helath is predominantly male-dominated, and extrapolating such data to female and/or people with a disability/para-athlete populations is challenging due to known physiological, psychological, and perceptual differences in these populations. Where available from the current literature, these differences are discussed within the chapter. However, further high-quality research is needed to determine female and people with a disability/para-athlete responses to hypoxia, heat, and cold. This research is essential to establish robust sex and disability-specific mechanisms an to create individualized best practice guidelines for health, safety, and performance within these populations. Intriguing data demonstrates that acclimation or acclimatization to heat or cold can alter, often favorably, subsequent physiological and cellular responses to hypoxia and vice versa (reviewed here; typically referred to as cross-tolerance). Limited data, particularly from a qhole-body human perspective, exist on the specific combined effects of heat or cold stimuli with hypoxia. This is surprising given the variety of occupational (mine workers at >= 3,000 m and leisure (mountain climbing/ultramarathons) pursuits where individuals encounter a combination of stressors. Within such pursuits, individuals may experience myriad combinations of heat and cold exposure along with varying levels of hypoxia. From an extreme athletic perspective, during the Ultra Trail du Mont Blanc, competitors experience 10,000 m of total elevation gain (up to a peak altitude of ~2,500 m) in combination with temperatures ranging from below 0°C to 30°C. In the real world, it is rare that a stressor (i.e., heat, cold, hypoxia) is experienced in isolation. High altitude (i.e., hypoxic environment) mountain ranges are synonymous with cold temperatures while some mountainous regions in Southeast Asia experience hot and humid climate. Despite the intrigue surrounding cross-tolerance, the specific purpose of this chapter ist to examine the combined effects of hypoxia and hot/cold stress on acclimation status or adaptations, exercise performance, and health. The impact of hot/ cold (e.g., air and water) alone on health, physiology, and exercise responses are well-characterized. The first section of this chapter will briefly describe these responses to temperature. However, the reader is directed tot he following resources for in-depth descriptions, analysis, and review oft he physiological and exercise responses to cold and heat. The subsequent focus will be on the combined effects of hypoxia and temperature. First, this includes a description on how to determine or quantify the effects of combined (hypoxia and temperature) versus individual (hypoxia/temperature alone) stressors on exercise and health. Second, the current knowledge surrounding the combined impact of hypoxia-and-cold and hypoxia-and-heat on exercise and health will be reviewed. Finally, a discussion oft he future research required in this space will be provided.